Electromyographic amplitude and coactivation of the core muscles during different unstable push-up exercises - Palma, F.; Perramont, N.; Rojas, V.; Bertolotto, B.; Tuesta, M. (Medicina dello Sport, 2021)
BACKGROUND: Currently, unstable push-ups are used to increase the activation of the muscles in the upper extremities and core muscles if compared to conventional push-ups. The aim was to examine the effects of different unstable push-ups on the electromyographic activity and coactivation of the core muscles. In addition, ascent and descent push-up phases were analyzed. METHODS: Twelve physically active men (age: 23.7±3.0 years old; body mass: 71.7±8.7 kg; height: 1.73±0.06 m; Body Mass Index: 23.9±2.4 kg/m2) carried out conventional and unstable push-up exercises (balance trainer, balance discs and suspended training) while electromyography signals of pectoralis major (PM), rectus abdominis (RA), external oblique (EO), longissimus (LS) and lumbar multifidus (LM) were assessed. The percentage of the maximum voluntary isometric contraction for all muscles was calculated. RESULTS: For muscle amplitude, suspended push-up caused greater muscular activation of the RA and EO in comparison to the other conditions (P<0.05), and a greater activation of the LS in comparison to conventional and balance disc push-ups (P<0.05). In relation to the push-up phases, only the EO showed a greater electromyographic activation during the ascent phase of suspended push-ups (P<0.05). Regarding muscle coactivation, it was observed that the RA/LM muscular pair showed lower values when the participants performed suspended push-ups in comparison to the conventional push-up. CONCLUSIONS: Suspended push-ups showed a greater electromyographic activation and a lower coactivation in comparison to unstable surface push-ups. We recommend that sport science professionals and practitioners include, with precaution, suspended push-ups into exercise routines to improve strength in the upper extremities and core balance.